Thickness measurement of dielectric films by wavelength scanning method - Köysal, O; Önal, D; Özder, S; Ecevit, FN (Elsevier Science Bv, 2002)
Thickness measurement of optically transparent thin films was done by multiple interference technique. Monochromator was used for wavelength scanning in the visible wavelength range to obtain transmittance of the single and two-layer films. When the wavelength dependence of the refractive index of the film is negligible in the measurement range, the discrete Fourier transform (DFT) technique can be applied to obtain film thickness. The measured thicknesses are compared with fringe counting and mechanical micrometer readings. The results have shown that the DFT technique is advantageous if the film has two or more layers. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: thin films; thickness; transmittance; Fourier transform